ALIENABLE AND INALIEANABLE NOUNS IN WANO - Willem Burung (Linguistik Indonesia, 2018)
This paper describes structural and distributional properties of alienable and inalienable nouns in Wano, a Trans-New Guinea language spoken in Papua by about 7,000 native speakers. I define differences between alienable and inalienable nouns in §2, where it will be apparent that they can be distinguished in terms of their (i) nominal generalisation (§2.1), (ii) lexical forms (§2.2), (iii) plurality coding (§2.3), (iv) possessive constructions (§2.4), and (v) head-role in a clause (§2.5). Alienable nouns are described in §3. Then in §4, I will demonstrate that inalienable nouns are: (i) restricted on vowel-initial words, and (ii) there is a clear morphosyntax-semantics-pragmatics interface reflected in kin terminologies. The kin term for 'child', for instance, is distinguished with respect to the sex of parents. In expressing the ownership of a child, a father will use the word nabut for the English 'my child' (inflection of: {n-abut} \1s-child.of.male\) and a mother will use nayak 'my child' (inflection of: {n-ajak} \1s-child.of.female\). Terms for kinship relations, body parts, cultural items, and experiential events are inalienably coded. Finally, words that are inalienably marked will be presented in §5.